Implementasi Model Pembelajaran Self Directed Learning dalam Pembelajaran PAI di Sanggar Bimbingan Kamus Gombak Utara Selangor Malaysia Tahun 2024 - Hidayah, Alifah Nur; Priarni, Rina; Matori, Matori (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2025)
The purpose of this research is to understand the implementation of the Self Directed Learning model in PAI education at SB Kamus Gombak Utara, and to identify the supporting and inhibiting factors. This research is a qualitative study that produces descriptive data obtained from observed individuals and behaviors. Data collection techniques through observation, interviews, and documentation. Based on the research results, the implementation of the SDL learning model in PAI education at SB Kamus Gombak Utara is considered good, with students experiencing an increase in knowledge, independence, and responsibility towards themselves and their peers, thereby achieving success in PAI education.